Accountability for The Performance of Temuwuh Village Government, Dlingo Sub-District, Bantul District, Special Region Of Yogyakarta - Suranto Suranto; Dyah Mutiarin; Awang Darumurti; Dwian Hartomi Akta Padma Eldo (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2019)
This article aims to explore the implementation of Village Government accountability in financial, administrative and policy aspects, by taking the object of research in Temuwuh Village, Dlingo District, Bantul Regency, DIY which is a representation of villages in the border region. The method used is a qualitative method with an exploratory approach, using depth interviews, FGD, observation and documentation in collecting . The results showed that the accountability of the performance of the Temuwuh Village Government had been running in accordance with applicable regulations, but it was not optimal. The community is still passive and has not been involved in the program and budget preparation process. The role of the community to be involved in the policy formulation process is also low, as well as the lack of administrative accountability due to the unavailability of SOPs and the support of adequate information systems.